Impact of Nuts Consumption on Blood Pressure, Glycemic Status, Lipid Profile and Total Protein in Healthy Human Volunteers - AL-Kass, Suad y.; Al-Habib, Omar A. M.; Jasim, Kajeen H. (Science Journal of University of Zakho, 2014)
To investigate the advantage of consumption of a mixture of almond and pistachio on blood pressure, lipid profile, sugar and protein levels in healthy volunteers. Subjects and Methods:This dietary intervention study was carried out during the period from February to March 2013. A total of 48 apparently healthy males students from Military Academy / Zakho, Kurdistan Region of Iraq participated in this study. All the students were living in a controlled environment. Blood samples were taken and analyzed for the determination of serum glucose, lipid profile, total protein, albumin and globulin. Parameters were obtained at baseline, 3 and 6 weeks after daily consumption of 50gm of almond and pistachio mixture. Results: The results of the current study demonstrated that daily consumption of 50 gs of almond and pistachio mixture for 3-6 weeks significantly ( P<0.05 – 0.001) decreased the diastolic blood pressure and the level of blood glucose , whereas body mass index (BMI) was not influenced at all. Serum total protein, albumin and globulin levels were significantly increased (P<0.05-0.005). Finally, Total cholesterol (TC), triglycerides (TG), low density lipoprotein-cholesterol (LDL-ch), very low density lipoprotein cholesterol ( VLDL-ch), TC/HDL and LDL/HDL were significantly decreased (P<0.05-0.005) after 6 weeks of nuts consumption, where as high density lipoprotein- cholesterol, was significantly increased (P<0.01). Conclusion: This dietary intervention trial, demonstrated that almonds and pistachio mixture improved blood glucose , total protein, and lipid profile to much better levels than that obtained previously using each one separately in healthy volunteers.